The influence of graphene on the mechanical, thermal, and flame retardant characteristics of Polyamide 6 - Sabet, M. (Taylor and Francis Ltd., 2021)
Graphene (G) was produced and melt-blended with polyamide 6 (PA6) to study the mechanical, electrical, and flame-hindrance characteristics of PA6-G compounds. It resulted that G is well dispersed in PA6 up to 2.0Â wt owing to electrostatic contact. A clear increment in degradation temperature and a drop in extreme degradation degree is detected from the thermogravimetric experiment for PA6-G compounds. The G inclusion to PA6 amended flame-protection of PA6-G compounds by delaying smoke density and reduction of flammable gas. This work proved an appropriate formulation of polymer/G compounds applied to engineering materials; develop the types of compounds with nano-additives. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.